Redesigning knowledge systems for urban resilience. Issue 101 (November 2019) - Feagan, Mathieu; Matsler, Marissa; Meerow, Sara; Muñoz-Erickson, Tischa A.; Hobbins, Robert; Gim, Changdeok; Miller, Clark A.
Abstract: While studies have suggested that climate change adaptation will require dynamic sets of knowledge types—scientific, technical, local, and tacit—about complex, interconnected problems across spatial and temporal scales, less attention has been directed to how these different ways of knowing might be used to transform specific urban knowledge systems that are currently in place, to align with diverse societal needs, and to open new pathways for designing how cities sense, anticipate, adapt to, and learn from extreme weather events. This special issue on knowledge systems for urban resilience explores the social practices that produce, validate, circulate, and use information, data, and expertise to enable institutions to adapt to the unpredictable and highly dynamic conditions of the Anthropocene. We are particularly interested in the relationship between the social organization of knowledge production and ways that cities can build urban resilience to extreme weather events associated with climate change. Through a combination of conceptual and case study analyses of how knowledge systems work in cities, we argue that building adaptive capacity requires changing the practices, rules, expectations, and underlying power relations in the production and use of knowledge.